2013
DOI: 10.1186/1868-7083-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition in the treatment of acute myeloid leukemia: the effects of valproic acid on leukemic cells, and the clinical and experimental evidence for combining valproic acid with other antileukemic agents

Abstract: Several new therapeutic strategies are now considered for acute myeloid leukemia (AML) patients unfit for intensive chemotherapy, including modulation of protein lysine acetylation through inhibition of histone deacetylases (HDACs). These enzymes alter the acetylation of several proteins, including histones and transcription factors, as well as several other proteins directly involved in the regulation of cell proliferation, differentiation and apoptosis. Valproic acid (VPA) is a HDAC inhibitor that has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 122 publications
1
89
1
1
Order By: Relevance
“…Obviously, elimination of TNF--mediated MMP-9 expression would be beneficial for suppressing the progression of leukemia. Some studies suggested that the HAT inhibitor could be useful for leukemia therapy [50,51]. Nevertheless, the use of HDAC inhibitors should be carefully evaluated because the data presented in this study show that TSA induces MMP-9 up-regulation in leukemia cells.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Obviously, elimination of TNF--mediated MMP-9 expression would be beneficial for suppressing the progression of leukemia. Some studies suggested that the HAT inhibitor could be useful for leukemia therapy [50,51]. Nevertheless, the use of HDAC inhibitors should be carefully evaluated because the data presented in this study show that TSA induces MMP-9 up-regulation in leukemia cells.…”
Section: Accepted Manuscriptmentioning
confidence: 83%
“…Several approaches to improving retinoid efficacy have been examined in experimental studies. These include combining ATRA with inhibitors of growth factor signaling pathways [45] as well as proteasome pathway inhibitors [46] and histone deacetylase inhibitors [47,48]. At least one novel retinoid (Tamibarotene) has been tested [49] and is currently under investigation in PML [50].…”
Section: Discussionmentioning
confidence: 98%
“…However, an alternative strategy could be to combine CDC25 inhibitors with low-toxicity disease-stabilizing strategies in patients that are unfit for the intensive and potentially curative treatment. If this last strategy is considered, CDC25 inhibitors may be combined with all-trans-retinoic acid (ATRA) plus valproic acid [167], low-dose cytarabine [168], hydroxyurea and/or 6-mercaptopurine [167][168][169][170][171].…”
Section: Combination Of Cdc25 Inhibitors With Conventional Chemotherapymentioning
confidence: 99%